2019
DOI: 10.3390/ijms20092271
|View full text |Cite
|
Sign up to set email alerts
|

HDAC1,2 Knock-Out and HDACi Induced Cell Apoptosis in Imatinib-Resistant K562 Cells

Abstract: Since imatinib (Glivec or Gleevec) has been used to target the BCR-ABL fusion protein, chronic myeloid leukemia (CML) has become a manageable chronic disease with long-term survival. However, 15%–20% of CML patients ultimately develop resistance to imatinib and then progress to an accelerated phase and eventually to a blast crisis, limiting treatment options and resulting in a poor survival rate. Thus, we investigated whether histone deacetylase inhibitors (HDACis) could be used as a potential anticancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In addition, at these concentrations, imatinib significantly inhibited K562 cell viability and cell proliferation by approximately 50% compared to the DMSO control, whereas only sgRNA_2 virus infection had a similar inhibitory effect on K562 cell viability ( Figure 7 E, p < 0.05). Our recent study showed that imatinib-resistant K562 cells (K562-IR) have a much higher IC50 value for imatinib treatment than wild-type K562 cells, with a 30-fold increase in drug sensitivity [ 25 ]. With the same cells, we did not find any mutations in the entire ABL gene through Sanger sequencing, indicating that BCR-ABL amino acid substitutions inside the kinase domain may not be the main cause of disruption in the interaction of imatinib and the tyrosine kinase domain, resulting in a loss of sensitivity to the drug in our long-term imatinib-treated K562-IR cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, at these concentrations, imatinib significantly inhibited K562 cell viability and cell proliferation by approximately 50% compared to the DMSO control, whereas only sgRNA_2 virus infection had a similar inhibitory effect on K562 cell viability ( Figure 7 E, p < 0.05). Our recent study showed that imatinib-resistant K562 cells (K562-IR) have a much higher IC50 value for imatinib treatment than wild-type K562 cells, with a 30-fold increase in drug sensitivity [ 25 ]. With the same cells, we did not find any mutations in the entire ABL gene through Sanger sequencing, indicating that BCR-ABL amino acid substitutions inside the kinase domain may not be the main cause of disruption in the interaction of imatinib and the tyrosine kinase domain, resulting in a loss of sensitivity to the drug in our long-term imatinib-treated K562-IR cells.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in silico predictions should be critically considered due to potentially different pharmacokinetic properties of compounds in vivo. Collectively, MAKV-8 appears to be an attractive drug candidate for further consideration in CML therapies, especially considering that the inhibition of HDAC1 and HDAC2, upregulated in LSCs versus HSCs from patients, strongly impacts the transcription of proteins essential for tumor cell survival [21].…”
Section: Discussionmentioning
confidence: 99%
“…8a). The importance of HDAC1 and HDAC2 in tumor cell survival provides a good rational for treating CML cells with imatinib in combination with pan-HDACis [21].…”
Section: Modulation Of Hdac Expression Profiles In CML Patientsmentioning
confidence: 99%
“…Interestingly, several members of the HDAC family are implicated in the development/maintenance of cancer stemness and fulfilment of the EMT program, while some HDAC inhibitors are suggested to be used against CSCs [ 338 , 339 ]. If HDAC inhibitors are capable of suppressing the EMT-associated generation of radioresistant and actively migrating CSC-like cells in hypoxic niches, such agents may sensitize hypoxic tumors to radiotherapy.…”
Section: How Do Epigenetic Regulators Affect the Radioresistance Omentioning
confidence: 99%